2020
DOI: 10.2337/db20-0394
|View full text |Cite
|
Sign up to set email alerts
|

The Mineralocorticoid Receptor Antagonist Eplerenone Suppresses Interstitial Fibrosis in Subcutaneous Adipose Tissue in Patients With Type 2 Diabetes

Abstract: Activation of the mineralocorticoid receptor (MR) may promote dysfunctional adipose tissue in patients with type 2 diabetes, where increased pericellular fibrosis has emerged as a major contributor. The knowledge of the association among the MR, fibrosis, and the effects of an MR antagonist (MRA) in human adipocytes remains very limited. The present substudy, including 30 participants, was prespecified as part of the Mineralocorticoid Receptor Antagonist in Type 2 Diabetes (MIRAD) trial, which randomized patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In this trial population, spironolactone also reduced circulating markers of fibrosis and blood pressure and improved cardiac structure and function, therefore suggesting a positive benefit–risk ratio 4 . Similar antifibrotic features were also found with high doses (100–200 mg/day) of eplerenone in another trial of patients with type 2 diabetes and a high cardiovascular risk, 17–19 as well as several trials of HF 8 …”
Section: Discussionsupporting
confidence: 70%
“…In this trial population, spironolactone also reduced circulating markers of fibrosis and blood pressure and improved cardiac structure and function, therefore suggesting a positive benefit–risk ratio 4 . Similar antifibrotic features were also found with high doses (100–200 mg/day) of eplerenone in another trial of patients with type 2 diabetes and a high cardiovascular risk, 17–19 as well as several trials of HF 8 …”
Section: Discussionsupporting
confidence: 70%
“…We measured the gene expression of both lipocalin 2 ( Lcn2 ), an MR target we previously identified in the cardiovascular system [ 29 ], and prostaglandin D2 synthase ( Ptgds ), that we identified as a novel MR target specific to the AT in mice and also—importantly—in obese patients [ 9 ]. These targets were recently shown to be modulated by MR in the AT of obese patients treated with eplerenone [ 30 ]. Gene expression of these two genes was induced in the epididymal visceral AT (EVAT) of Adipo-MROE mice, indicating that MR overexpression in adipocytes is associated with MR overactivation, as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Improvement in left ventricular hypertrophy and structural remodeling through the use of MRAs has been confirmed in clinical research (Maron and Leopold, 2010;Leung et al, 2013). Johansen et al found that eplerenone suppresses interstitial fibrosis in the subcutaneous adipose tissue of patients with type 2 diabetes (Johansen et al, 2021). Mahajan et al found that eplerenone improved hemodynamic and ventricular dysfunction in streptozotocin (STZ)-isoproterenol-challenged rats (Mahajan et al, 2018).…”
Section: Introductionmentioning
confidence: 93%